Sexual Dysfunction in Persons With Substance Use Disorders. Issue 2 (April 2019) - Ghadigaonkar, Deepak S.; Murthy, Pratima
Abstract: Sexual dysfunction is commonly associated with the use of substances, in both men and women. This area requires prominent attention, particularly as the use of substances is often with the expectancy of improving an underlying sexual dysfunction or with a positive expectancy of enhancing sexual function. The chronic use of substances has a negative impact on sexual function and causes various kinds of sexual dysfunction in both men and women. In this narrative review, we look at the effect of various substances of abuse on sexual functioning and discuss management strategies in such situations.